VIRTUAL AND AUGMENTAL REALITY IN THE ART-WORKS OF UKRAINIAN ARTISTS - Міронова, Т. В. (Art and Design, 2021)
The purpose of the publication is to analyze the virtual and augmented reality in the work of Ukrainian artists of the last thirty years. The study digital visual art space is the analytical methods to determine internal trends and prospects of contemporary Ukrainian art. The main methodological approach is the cultural-semiotic analysis of the forms of manifestation of visualization of modern art culture. The application of a systematic approach allowed to study semiotic systems that contribute to the comprehensive disclosure of the problem of semantics of modern forms of visualization. The peculiarities of the use of technologies for the support and demonstration of works of art are revealed, the emphasis is on the emergence of new digital trends in contemporary art, thanks to which visual works function in their own media environment. Virtual and digital realities in the fine arts replace the artist’s canvas, and the ironer allows him to immerse himself in other unreal worlds of the author’s subconscious. Thus, from a simple fascination with technology, the modern generation of artists quickly moved to quality and content requirements, conceptuality and communication between the author, viewer and work of art, which requires artists to understand modern technology, traditional techniques of painting. The scientific novelty of the work is to identify the main characteristics of the development of modern visual arts with the help of virtual space in the Ukrainian cultural environment. The practical significance of the obtained results is that they can be used as a factual and theoretical basis for the creation of relevant sections in scientific and scientific-methodical publications on the history of contemporary Ukrainian art.